CASE OF PNEUMOMEDIASTINUM AND SURGICAL EMPHYSEMA IN A PATIENT WITH COVID-19 PNEUMONIA, ON CPAP - Idrees, Muhammad; Abdulmumeen, Abdulfatahi; Khan, Munir (Journal of Ayub Medical College Abbottabad, 2022)
An unusual case of a 35-year-old woman with COVID-19 pneumonia who suddenly desaturated while on continuous positive airway pressure leading to pneumomediastinum and surgical emphysema thereby requiring ventilatory support in intensive therapy unit. It is unclear from history and clinical assessment; whether this complication was directly related to COVID-19 pneumonia and it worsened with the initiation of CPAP, OR it was a direct complication of CPAP.